Sociocultural Framework: Emotional Geographies of a Female EFL Teacher in 3T Area - Sri Rejeki; Diah Kristina; Nur Arifah Drajati (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Teaching English in EFL context needs more than the knowledge of subject matter and pedagogical skill but also its emotional side. Teacher emotion is one of necessary aspect that could not be left behind. An EFL teacher who teaches English in 3T areas in Indonesia encountered some challenges such as geographical feature, culture, poor quality of both students and teachers, and so on. This research paper tries to find out teacher emotions experienced by female teacher in one of 3T areas. This research will explore the distance and closeness felt by the teacher while teaching English there. This research was conducted using a narrative case study method. The data were collected from the participant’s journal and interview. Referring to Hargreaves framework, the findings reveal 5 emotional geographies of the participant namely sociocultural, political, moral, spatial, and professional. This research contributes to Indonesian government as the one that concerns in 3T areas. It is also significant data for EFL teachers who have to handle complex situations while teaching in such context.